Yield of Tibial Lengthening Surgery using NA External Fixator - Syed Asif Ali, Yasir Iqbal, Shahzad Anjum, Muhammad Ali, Shandana Yousafzai, Muhammad Ikramullah Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the yield of tibial lengthening procedure using NA external fixator in our patients at GMC, Gujranwala, and KEMU, Lahore, Pakistan. In addition, this study will also find significant factors associated with success of the NA fixator-assisted lengthening surgery. Methods: This cross-sectional analysis include patients having short tibia who underwent tibial lengthening procedure using NA external fixator. These patients were categorized int two groups: successful lengthening and unsuccessful lengthening procedure groups. Statistical analysis was done using SPSS version 25. Independent sample T test, Chi-square test, and binary logistic regression analysis were applied. The p-values were taken statistically significant if < 0.05. Independent sample T test and Chi-square test for independence were used for quantitative and qualitative variables respectively to determine their significant association with the success of the tibial lengthening procedure. The p-values were taken statistically significant if <0.05. Results: Amongst 100 patients, healing occurred, and lengthening achieved in 94% and healing did not occur in 6%. The duration of hospitalization was statistically significantly less among the patients in which lengthening procedure was successful as compared to the patients in which lengthening procedure was not successful (4.83±3.44 days vs 11.00±5.59 days, p<0.01). All 6 patients in which lengthening procedure was not successful got no plaster on fixator removal (p<0.01). The skin reactions to the pins was significantly less among the group of the patients in which lengthening procedure was successful as compared to the group of the patients in which lengthening procedure was unsuccessful (p=0.027). Tibial lengthening procedure was significantly unsuccessful among the patients who received bone grafting during lengthening procedure (p<0.01). Conclusion: The yield of tibial lengthening procedure using NA external fixator was excellent in our studied population. Duration of hospitalization as well as the reaction to pins was significantly higher among the patients in which lengthening procedure was unsuccessful. Similarly, the unsuccessful tibial lengthening procedure was significantly common for the patients who received bone grafting during lengthening procedure.